2021
DOI: 10.1093/nar/gkab386
|View full text |Cite
|
Sign up to set email alerts
|

SANS (USH1G) regulates pre-mRNA splicing by mediating the intra-nuclear transfer of tri-snRNP complexes

Abstract: Splicing is catalyzed by the spliceosome, a compositionally dynamic complex assembled stepwise on pre-mRNA. We reveal links between splicing machinery components and the intrinsically disordered ciliopathy protein SANS. Pathogenic mutations in SANS/USH1G lead to Usher syndrome—the most common cause of deaf-blindness. Previously, SANS was shown to function only in the cytosol and primary cilia. Here, we have uncovered molecular links between SANS and pre-mRNA splicing catalyzed by the spliceosome in the nucleus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 86 publications
5
40
0
Order By: Relevance
“…In particular, the latter study shows that SANS causes the retention of exon 11, thereby leading to alternative expression of the human harmonin a1 and a4 transcripts. Further studies are needed to understand the interplay and interference of the two USH1 proteins, SANS and harmonin, in the retina at two different levels: in common protein complexes (SANS-SAM/PBM binding to the N-terminal HHD/PDZ1 and PDZ3 of harmonin), possibly related to transport processes (Adato et al, 2005; Maerker et al, 2008; Yan et al, 2010), and during splicing where SANS presumably can interfere with USH1C /harmonin pre-mRNA (Yildirim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the latter study shows that SANS causes the retention of exon 11, thereby leading to alternative expression of the human harmonin a1 and a4 transcripts. Further studies are needed to understand the interplay and interference of the two USH1 proteins, SANS and harmonin, in the retina at two different levels: in common protein complexes (SANS-SAM/PBM binding to the N-terminal HHD/PDZ1 and PDZ3 of harmonin), possibly related to transport processes (Adato et al, 2005; Maerker et al, 2008; Yan et al, 2010), and during splicing where SANS presumably can interfere with USH1C /harmonin pre-mRNA (Yildirim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, USH1C /harmonin has not been identified as a target for the splicing control machinery of Musashi proteins. Recently, we were able to show that the USHG1 protein SANS interacts with core components of the spliceosome and regulates splicing including constitutive and alternative splicing of USH1C /harmonin (Yildirim et al, 2021). In particular, the latter study shows that SANS causes the retention of exon 11, thereby leading to alternative expression of the human harmonin a1 and a4 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…The splicing factor SON was reported to be required for centrosome assembly and ciliogenesis ( Stemm-Wolf et al, 2021 ). The ciliopathy protein SANS/USH1G, mutations of which lead to Usher syndrome, was shown to regulate pre mRNA splicing and interact with splicing factors SON and SF3B1 ( Yildirim et al, 2021 ). SANS is required for the transfer of tri-snRNPs between Cajal bodies and nuclear speckles which are critical for spliceosome assembly.…”
Section: Spliceosome Involvement In Ciliary Diseases Like Retinitis P...mentioning
confidence: 99%
“…SANS is required for the transfer of tri-snRNPs between Cajal bodies and nuclear speckles which are critical for spliceosome assembly. Furthermore, its depletion or pathogenic SANS mutations were shown to affect the splicing of genes important for cell proliferation and Usher syndrome ( Yildirim et al, 2021 ). An additional layer of complexity was recently discovered by Herve LeHir and colleagues who reported that the exon-junction complex (EJC) is required for ciliogenesis in neural stem cells by accumulating to ciliary bodies and recruiting mRNAs important for centrosome organization ( Kwon et al, 2021 ).…”
Section: Spliceosome Involvement In Ciliary Diseases Like Retinitis P...mentioning
confidence: 99%
“…In cooperation with MFAP1/Spp381, UBL5/Hub1 likely plays a role in stabilizing the position of 5 -exon and the interaction of U5 snRNA within the pre-catalytic and activated spliceosomal complexes [30]. As UBL5/Hub1, SART1/Snu66, and MFAP1/Spp381 are present in foci in close proximity to-but not entirely overlapped with-the Cajal bodies, which is involved in the assembly and recycling of snRNPs [32][33][34][35][36], it is tempting to speculate that they might contribute to the processes. It is also important to note that MFAP1/Spp381 interacts with UBL5/Hub1 via the HIND-interacting surface in a mutually exclusive manner (Figure 2C) [30].…”
Section: Pre-mrna Splicingmentioning
confidence: 99%